2021
DOI: 10.1007/s12149-021-01686-5
|View full text |Cite
|
Sign up to set email alerts
|

13N-ammonia positron emission tomography-derived left-ventricular strain in patients after heart transplantation validated using cardiovascular magnetic resonance feature tracking as reference

Abstract: N-ammonia positron emission tomography-derived left ventricular strain in patientsafter heart transplantation validated using cardiovascular magnetic resonance feature tracking as reference

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This method was also used to evaluate right ventricular myocardial longitudinal strain to detect reduced right ventricular myocardial motion due to ischemia in the right coronary artery territory (29). Separately, Kawakubo et al evaluated the LV strain in heart transplant patients and validated 13 N-ammonia PET strains using CMR feature tracking strains (29). Compared with previous studies, our study validates PET MPI-derived strain measurements with resting 2D TTE-derived strain.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This method was also used to evaluate right ventricular myocardial longitudinal strain to detect reduced right ventricular myocardial motion due to ischemia in the right coronary artery territory (29). Separately, Kawakubo et al evaluated the LV strain in heart transplant patients and validated 13 N-ammonia PET strains using CMR feature tracking strains (29). Compared with previous studies, our study validates PET MPI-derived strain measurements with resting 2D TTE-derived strain.…”
Section: Discussionsupporting
confidence: 55%
“…The use of PET imaging to measure LV strain has not been well established for routine clinical practice, but some publications demonstrated PET study-derived stain in potential clinical settings. Recent publications from Kawakubo et al (28,29) showed the utility of 13 N-ammonia PET MPI to measure LV strain. They studied endocardial strain and used it to compare blood flow and myocardial motility in ischemic patients (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time resolution is an important factor in strain analysis, and the 16 frames/cycle time resolution is inferior to echocardiography, making strain rate evaluation difficult. However, PET strain has been proven to have a significant correlation with cine MRI strain with comparable temporal resolution of 20 frames/cycle (9). In terms of objectivity and reproducibility, it is considered to be no less than echocardiography.…”
Section: Discussionmentioning
confidence: 99%